COMPETENCE AND LITERACY AS A MODEL FOR THE DEVELOPMENT OF COMPETITIVE MILLENNIAL FARMERS IN PURWOREJO REGENCY - Wakhdan Wakhdan; Adi Sucipo; Nur Siyami (Sean Institute, 2023)
Facing the era of Society 5.0 and the development of technological advances, business strategy is essential to measure effectiveness and efficiency. Towards Era 5.0, human work and activities will focus on Human-Centered which is based on technology. Facing this phenomenon and the incessant discussion about millennial farmers, understanding literacy for farmers is fundamental, starting from understanding competence and literacy. This study uses a qualitative approach. The population in this study are all millennial farmers who are members of the catalogue list of millennial farmers in Purworejo Regency obtained from the Food Security and Agriculture Office of Purworejo Regency in 2022, a number of 40 people who were then sampled for this study with a sampling technique using purposive sampling, namely by criteria for millennial farmers who meet the criteria of millennial farmers, have complete data that support research activities and millennial farmers who are willing and committed to joining the millennial farmer forum in Purworejo Regency so that a total sample of 9 people is obtained. As for the results of this study, the factors that influence the lack of interest consist of the image of the agricultural sector which is less prestigious, high risk, less guaranteeing the level of stability, and income continuity; the average land tenure is narrow; Diversification of non-agricultural businesses and agricultural industries in less/undeveloped villages; Succession of farming management is low; There is no particular incentive policy for young/beginner farmers; and The changing perspective of youth in the postmodern era like now. The strategies carried out include providing correct information about agriculture and the world of agriculture is interesting; Promoting the let's build village program and prepare supporting facilities/infrastructure; Encouraging the formation of community groups and their guidance by the government or non-governmental organizations; and Creating collaboration between government, academia, banking and core businesses/farmers. Regarding competence and literacy, the millennial farmer actors in Purworejo Regency already have good competence and literacy towards Competitive Millennial Farmers.